Analisis Pengembangan Produk Unggulan Daerah (PUD) Kabupaten Kendal - Hermawan Budiyanto (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
The research is aimed at finding out the issues related to the development of the region's leading product in the district of Kendal. The type of research used in this study is qualitative. The analysis used is SWOT analysis whose output is a strategy and policy of development of PUD. Development of regional superior product (PUD) is an important strategy in optimizing local and regional economic potential. This abstract presents a brief overview of the concepts, strategies, influencing factors, as well as the impact of PUD development. The PUD concept emphasizes the identification and utilization of local advantages of a region, whether in the form of cultural wealth, natural resources, or specialized expertise. PUD's development strategy includes measures such as identifying local potential, improving product quality and innovation, effective marketing, and cooperation and collaboration between governments, entrepreneurs, and other stakeholders. A number of factors influence the success of PUD development, including the availability of resources, government regulations and policies, technology and innovation, market access, and effective leadership and management. Success in developing PUD can have a positive impact in terms of empowering the local economy, enhancing the tourism sector, and growing the regional economy as a whole.This abstract highlights the importance of PUD development as a means of improving the competitiveness and well-being of local communities, while promoting economic sustainability and the preservation of the cultural heritage of the region. May this abstract give a clear picture of the importance of developing regional excellence products. If you need more information or specific adjustments, do not hesitate to contact me.